2023
DOI: 10.3390/jcm12103557
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant Autoimmunity in Endometriosis Impairs Endometrium–Embryo Crosstalk at the Implantation Site: A Multicenter Case-Control Study

Abstract: Endometriosis and autoimmune diseases share a hyper-inflammatory state that might negatively impact the embryo–endometrium crosstalk. Inflammatory and immune deregulatory mechanisms have been shown to impair both endometrial receptivity and embryo competence at the implantation site. The aim of this study was to investigate the potential additional impact of co-existing autoimmunity in women affected by endometriosis on the early stages of reproduction. This was a retrospective, multicenter case-control study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 47 publications
(55 reference statements)
0
5
0
Order By: Relevance
“…Autoimmunity may not only enable the endometriosis appearance, but it also appears to have an in uence on endometriosis ndings. According to Almeri et al [10] the coexistence of autoimmunity in patients with endometriosis may have an additive role in problems with embryo implantation, favouring infertility in this situation. Infertility is one of the major concerns in endometriosis affecting from 30-50% of women with this disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Autoimmunity may not only enable the endometriosis appearance, but it also appears to have an in uence on endometriosis ndings. According to Almeri et al [10] the coexistence of autoimmunity in patients with endometriosis may have an additive role in problems with embryo implantation, favouring infertility in this situation. Infertility is one of the major concerns in endometriosis affecting from 30-50% of women with this disease.…”
Section: Discussionmentioning
confidence: 99%
“…[1] Autoantibodies recognizing endometrial antigens resulting from polyclonal B cell activation have also been documented in this setting. [1,[4][5][6] Other systemic and organ-speci c autoimmune diseases associated with endometriosis include systemic lupus erythematosus, [7] rheumatoid arthritis, [8] and Hashimoto thyroiditis, [9] in ammatory bowel disease, [10] and psoriasis. [10] The objective of this study was to examine the prevalence of autoantibodies such as antinuclear antibodies (ANA), antiphospholipid antibodies and anti-endomysial autoantibodies in the sera of patients with endometriosis.…”
Section: Introductionmentioning
confidence: 99%
“…However, in endometriosis, estrogen-mediated signaling abnormalities may lead to decreased endometrial receptivity, impacting embryo implantation and reducing pregnancy rates in mice [ 89 , 90 ]. It was also reported that immunological and inflammatory mechanisms in endometriosis have a significant additive negative impact on embryo implantation [ 91 ]. Within this process, NK cells may play a crucial regulatory role.…”
Section: Estrogen–nk Cells In Endometriosis-related Infertility and M...mentioning
confidence: 99%
“…This observation aligns with the growing understanding of endometriosis as a multisystem condition characterized by diverse genetic and somatic traits [ 127 , 128 ], along with a significant association with various comorbidities, primarily autoimmune [ 129 ] and immune-related diseases [ 130 ], but also fibromyalgia [ 131 ], migraine [ 132 ], and multiple pregnancy-related disorders [ 133 , 134 , 135 ]. The etiology of these comorbidities, whether resulting from a shared pathogenesis or the chronic inflammatory response to the endometriotic lesions, remains unknown [ 136 ], although the severity of endometriosis is known to increase with the co-occurrence of comorbidities [ 137 , 138 , 139 ].…”
Section: Microbiota In Endometriosismentioning
confidence: 99%